PENERAPAN STRATEGI QUANTUM LEARNING UNTUK MENINGKATKAN KECERDASAN INTERPERSONAL DAN INTRAPERSONAL - Arnis Susanti (DIADIK, 2023)
The purpose of this study was to describe the application of Quantum Learning Strategy to improve Interpersonal and Intrapersonal Intelligence in Hamasah Kindergarten, Bengkulu City. The research design used is Classroom Action Research and Quasi Experiment Class. The research subjects for the CAR were the children of Group B1 TK Hamasah Bengkulu City in the odd semester of the 2021/2022 academic year. For the quasi-experimental sample, the children of Group B2 TK Hamasah Bengkulu City. The research instrument used an observation sheet, the research data were analyzed by descriptive statistics, the average (mean), percentage, and t-test. The results showed that the implementation of the Quantum Learning Strategy could improve the Interpersonal and Intrapersonal Intelligence of Group B in Hamasah Kindergarten, Bengkulu City